Estudo da interação do polifosfato de sódio com íons metálicos divalentes e quitosana com aplicação em biocatálise. - Melo, Ana Danielle de Queiroz (2018)
The electrostatic interaction between species, sodium polyphosphate and metal ions can be confirmed by the promotion of coacervate in the reactive environment, both in the simple coacervation tests (interaction between sodium polyphosphate and a divalent salt), as well as in the tests of mixed coacervation (interaction between sodium polyphosphate and two divalent salts). In both cases a dependence of the properties of the coacervates obtained with the choice of the salt(s) chosen was observed. The properties of ionic radius and enthalpy of hydration have been shown themselves to be essential to understand the interaction between sodium polyphosphate and the chlorides of Ca2+, Mg2+, Mn2+, Co2+, Cu2+ and Zn2+, where ions that formed coacervates were naturally named as forming ions - Ca2+, Mg2+ and Mn2+ - with enthalpy values that reveal low interaction with water, while the ions that do not form coacervate were assembled together into another group - Co2+, Cu2+ and Zn2+. However, when added in the combined form (nonionic formator - ion formator), it happened the formation of coacervate for most of the tests without the need of additives. Enzymes serve as biocatalysts for many important reactions; however, their application has limitations, which could be overcome by using appropriate immobilization strategies. Here, a new support for immobilizing enzymes is proposed. This hybrid organic-inorganic support is composed of chitosan—a natural, nontoxic, biodegradable, and edible biopolymer—and sodium polyphosphate, the inorganic component. Lipase from Candida antarctica (CAL B) was immobilized in microspheres by encapsulation using these polymers. The characterization of the composites (by infrared spectroscopy, thermogravimetric analysis, and confocal Raman microscopy) confirmed the hybrid nature of the support, whose external part consisted of polyphosphate and the core is composed of chitosan. The immobilized enzyme had the following advantages: possibility of enzyme reuse, easy biocatalyst recovery, increased resistance to variations in temperature (activity declined from 60°C and the enzyme was inactivated at 80°C), and increased catalytic activity in the transesterification reactions. The encapsulated enzymes were used as biocatalysts for transesterification reactions to produce the compound responsible for the jasmine aroma.